Karya Ilmiah Sejarah Penerbangan Bandar Udara di Indonesia dari Tahun Ke Tahun - Haryanto, Haryanto; Silalahi, Amarson Felix; Hidayat, Agung Maulana; Natalius, Imron; Fadhillah, Raihan; Ardian, Wahyu (CV. ITTC INDONESIA, 2022)
Since the Dutch East Indies period in 1913, flights have been taking place in Indonesia. At first, the flight was not for commercial (civil) purposes but for military purposes. There were at least two factors that led to the development of military aviation at that time. First, namely the increase in technological findings that are increasingly sophisticated, especially in Europe and the USA, which became the forerunner to the establishment of airports. The next factor was competition during the Dutch administration, including when Japan won Russia in 1905. Along with military aviation, which began with the emergence of commercial public transportation modes, they contributed to reviving the Indonesian aviation industry. Indonesia's aviation map changed when the Japanese arrived in 1942. In the end, it was Indonesian warplanes that benefited. the physical revolution, which took place between 1946 and 1949. They cleverly used the legacy of Japanese-made aircraft to their advantage. The 1950s were the darkest days of commercial aviation. This is the moment and turning point in the development of commercial and domestic military aviation into the industry as it is today.